Triangle fire [videorecording (DVD)] - Wignot, Jamila; Wignot, Jamila; Murphy, Michael, 1938- (American experience, 2011)
The fire that tore through the Triangle Shirtwaist Factory in New York City on March 25, 1911, was the gruesome culmination of years of unrest in America's most profitable manufacturing industry. Two years earlier, led by a spontaneous walkout in the same factory, twenty thousand garment workers, in the largest women's strike in American history, took to the streets of New York to protest working conditions. They gained the support of both progressives and leading women in New York's society.